Peer-supported collaborative inquiry in teacher education: exploring the influence of peer discussions on pre-service teachers' levels of critical reflection. Issue 2 (3rd April 2019) - McGarr, Oliver; McCormack, Orla; Comerford, Jason
Abstract : Scaffolding pre-service teachers to critically reflect on their practice remains a challenging goal. Exploring the extent to which peer discussion facilitates this critical reflection is the focus of this paper. Using a series of three linked tasks, pre-service teachers 1) reflected on a classroom incident from a vignette of practice, 2) shared and discussed their initial reflections with peers and 3) revisited their initial reflection in an attempt to unearth any assumptions they may have had. The study found that peer discussion broadened pre-service teachers' perspectives beyond the initial ego-centric reflections, which were dominated by issues of pupil management, control and discipline. The peer discussion process supported pre-service teachers in identifying and questioning some of their preconceived assumptions. However, findings indicate that the process supported pre-service teachers in acquiring greater breadth rather than greater depth in reflective thinking. We would argue that rather than seeing peer engagement opportunities as a panacea, it should be viewed as a valuable scoping exercise to unearth alternative perspectives and to begin the process of 'hunting assumptions'.